PENGARUH PERMAINAN MENYUSUN PUZZLE BERKELOMPOK TERHADAP PERKEMBANGAN KERJASAMA ANAK USIA DINI - Didah Siti Faridah; Abdul Azis; Indrawati Noor Kamila (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2019)
This study aims to determine the improvement in the development of children's cooperation after using puzzle media in learning activities. The research method used is the Classroom Action Research (CAR) method. The data collection technique used was observation. The data collection instruments used were the teacher performance observation sheet in the preparation of the Daily Learning Implementation Plan (RPPH), the teacher's performance observation sheet in the implementation of learning, and the observation sheet on the development of children's cooperation. After analyzing the data, the researchers obtained the following conclusions: (1) The teacher's performance in the implementation of learning has increased, namely in cycle 1 with an average value of 3.28 (good), in cycle 2 with an average value of 3.9 (very well). (2) The ability of children's cooperation increases, namely in cycle 1 there are 8 children (57, 1%) developing according to expectations, in cycle 2 there are 8 children (57.1%) developing according to expectations, there are 5 children (36%) developing very well.